Determinants Of Telecommuting Among Women Workers In Penang: A Case Study. - Karia, Noorliza; Asaari, Muhammad Hasmi Abu Hassan (Universiti Sains Malaysia, 2014)

(untitled)
Telecommuting has been sought out from the women workers in Penang. This case study will identify the determinants that contribute to telecommuting acceptance among women workers. Interestingly, women workers did not indicate their acceptance toward the concept implementation. They will on consider telecommuting if they have to take care family matters. Therefore a huge efforts need to be carried out in making a paradigm change among women workers to accept the idea of telecommuting.